Parent-led school feeding: A tested approach to improve learning in schools - Budget Monitoring and Accountability Unit (Budget Monitoring and Accountability Unit, 2019)
Up to eight million children attend school in Uganda, however the largest proportion go hungry, with only 33% of the children receiving meals at school. This has implications on cognitive development, school performance and achievement (National Planning Authority Report, 2017). According to the Uganda Bureau of Statistics (UBOS-2014), 66% of learners at primary level were not feeding at school. Urban children (41%) are more likely to receive school meals than their rural counterparts (32%) and most of this feeding is provided through parental contribution. The Government of Uganda through the Ministry of Education and Sports (MoES) recognizes that feeding is an essential component of a child friendly school as it improves physiological growth, school enrolment, learning and overall cognition. In 2013, government designed the school feeding and nutrition guidelines to improve child health, nutrition and educational performance, however many schools are still unable to implement them. Additionally, in one of the Cabinet memos, the MoES stated that hunger is one of the main reasons children perform poorly in Universal Primary Education (UPE) schools. It noted that hungry children have poor concentration and mental abilities, absenteeism, bad behavior, poor health and end up dropping out of school. Parent-led feeding is the best option. This policy brief highlights; interventions undertaken to promote parent led school feeding and lessons learnt. It also provides policy recommendations.